2017
DOI: 10.1111/jocn.14019
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and specific characteristics of hospitalised pressure ulcer patients: A multicentre cross‐sectional study

Abstract: The survey could make managers know their prevalence level of pressure ulcers and provide priorities for clinical nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
13

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 30 publications
(50 reference statements)
4
31
0
13
Order By: Relevance
“…Similarly, the prevalence of pressure ulcers at one regional medical centre in eastern Thailand in 2008 was 9.58 per 1000 patient days (Kitkaew et al 2011). This rate was higher than the hospital-acquired pressure ulcer rate at unit level in the US hospitals in 2013 of 1.87-2.23% (Boyle et al 2016) or 1.26% in the Chinese hospitals (Zhou et al 2018).…”
Section: Introductionmentioning
confidence: 60%
“…Similarly, the prevalence of pressure ulcers at one regional medical centre in eastern Thailand in 2008 was 9.58 per 1000 patient days (Kitkaew et al 2011). This rate was higher than the hospital-acquired pressure ulcer rate at unit level in the US hospitals in 2013 of 1.87-2.23% (Boyle et al 2016) or 1.26% in the Chinese hospitals (Zhou et al 2018).…”
Section: Introductionmentioning
confidence: 60%
“…The association between incontinence and PI was significant. According to prior studies (Lachenbruch, Ribble, Emmons, & Vangilder, 2016;Zhou et al, 2017), incontinence was associated with an increased risk of PI. The relationship can be explained through the following reasons.…”
Section: Discussionmentioning
confidence: 94%
“…Referring to similar hospital based studies we estimated 100 patients were needed to ascertain the quality, accessibility and value of the data. 23 This study is reported in accordance with the RECORD Guidelines from the Equator Network. 25 Setting: The target community was chosen because it was the most socially and culturally diverse in the local health system area, with 17 ethnic groups and 79 languages being spoken.…”
Section: Methodsmentioning
confidence: 92%
“…22 Newer evidence now recognise the potential role of various data including standard laboratory tests (such as albumin levels), patient-reported symptoms, patient characteristics and comorbidities. 21,22,23 Some of these parameters are better suited to hospitalised patients who undergo regular blood tests, skin tests and intentional rounding , not PI patients living in their own homes. Such evidence suggests that information on wider patient characteristics, rather than purely medical information could be useful in the population of community PI patients that is predicted to grow.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%